Application of Thin Spray-on Liners for Rock Surface Support in South African Mines – A Review - Jjuuko, Samuel; Kalumba, Denis (Int J Innov Res Adv Eng, 2016)
Statistical data on fatalities in the South African mining industry indicate that the conventional surface support methods, such as mesh and shotcrete, need to be replaced with an alternative method. This is in order to meet the safety target of zero harm. To realise this, the industry since 1996, has fronted Thin Spray-on Liner as the alternative surface support method. In this paper, Thin Spray-on Liners are defined and their support mechanisms and application in mines are reviewed. In addition, benefits accruing to the local industry from their use are also discussed. The paper concludes by identifying directions for future research required to advance their usage.
Keywords: Rock surface support; Thin spray-on liners; Shotcrete and mesh; Mining safety; Rockfalls